Is There an Organizational Multiplier? - Hicks, Herbert G.; Graves, Benjamin B. (Academy of Management Journal, 1963)
The article presents information on a study on the impact of organizational multiplier, which stems from the natural tendency among individuals within organizations to try to act in ways which maximize their own welfare. A discussion is presented about the effects of the multiplier on the overall effectiveness of the organization. An overview of the tenet of the multiplier principle is presented, along with illustrations of the workings of the multipliers and mathematical expression of the multiplier.